Bird species richness, assemblage density, and feeding guild composition in human-modified lowland rainforests of Papua New Guinea - Kryštof Korejs; Bonny Koane; Samuel Jeppy; Legi Sam; Kateřina Sam (Journal of Field Ornithology)
The island of New Guinea is home to the third largest continuous rainforest in the world, which is increasingly threatened by large-scale deforestation and forest conversion. Despite this, there is little scientific data on the highly biodiverse local avifauna and in particular on its response to anthropogenic disturbances. We seek to address this problem by examining bird assemblages in human-altered rainforests in lowland Papua New Guinea. We surveyed birds using point counts (N = 160 over 90 survey days) in four forest types: a continuous primary forest control site; secondary forests regrown after small-scale agriculture; primary forest fragments isolated by logging; and secondary forests regrown after clear-cutting. We employed generalized linear mixed-effects models to analyze bird species richness, assemblage density, and community structure. We found that total bird species richness decreased significantly in all human-modified forests, while total density did not. Moreover, we found that different feeding guilds showed contrasting response to disturbances. Small-scale agriculture resulted in slight decreases of insectivore species richness but did not impact other guilds. However, in primary forest fragments, habitat isolation and loss of forest connectivity severely impacted both insectivores and frugivores. Moreover, in secondary forests regrown after clear-cutting, fragmentation was compounded with changes to forest structure, resulting in collapse of insectivore species richness and density. On the other hand, nectarivores responded positively to forest alteration, with increased assemblage density in all human-modified forests. Our results show that changes to forest structure come second to fragmentation in their negative effects on bird species. Retaining connectivity with contiguous primary forests is crucial for maintaining the bulk of avian biodiversity. As logging concessions expand across Papua New Guinea, conserving large, intact forest reserves will be essential for sustaining the region's unique avifauna.